PENGEMBANGAN SISTEM ENERGI TERBARUKAN: PENDEKATAN MULTIGENERATOR DAN SIMULASI ETAP - Kiswantono, Agus (Universitas Lampung, 2024)
This research focuses on the analysis of power flow in an electrical energy system involving 5 generators, with a nominal voltage of 345 KV, and a total power of 500 MW. Utilizing the ETAP simulation software, we evaluated the distribution of power, currents, and power factor across the entire system. The results of the analysis provide deep insights into the system's response to loads, power flow, and the efficiency of electrical power utilization. At the 345 KV voltage level, the simulation demonstrates the system's capability to maintain stability and power balance effectively. Power distribution and currents among generators provide a clear overview of the performance of the electrical network. Power factor analysis offers additional information regarding the efficiency of electrical power usage within the system. These findings serve as a crucial foundation for making informed decisions in managing and developing renewable energy infrastructure. In the era of transitioning towards more sustainable energy sources, a comprehensive understanding of power flow and system responsiveness to loads is essential to ensure the reliability and efficiency of the electrical power system